(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
Benzimidazoles are systemic fungicides that disrupt fungal energy metabolism by binding with high affinity to β-tubulin, thereby interfering with microtubule assembly. Resistance to this group of fungicides is primarily associated with alterations in the β-tubulin gene that reduce fungicide binding. Single-point mutations, especially at codon 198 (GAG→GCG, resulting in the E198A substitution), are among the most frequently reported mechanisms. Similar substitutions at other amino acid positions in β-tubulin have also been linked to resistance in several plant pathogenic fungi, including Botrytis cinerea, Helminthosporium solani, and Tapesia acuformis, as well as in various field-resistant populations. In Fusarium fujikuroi, resistance has been associated specifically with mutations in the β2-tubulin (β2tub) gene rather than β1-tubulin (β1tub). A Tyr50Asp substitution in β1-tubulin has been shown to confer resistance in UV-induced mutants of Fusarium moniliforme. Additional mutations such as Phe167Tyr, Glu198Ala, Glu198Val, Glu198Gly, and Phe200Tyr have been reported in F. graminearum, Helminthosporium solani, and other phytopathogenic fungi, further demonstrating the diversity of resistance-associated substitutions within the β-tubulin gene. In F. asiaticum, a point mutation at codon 198 in the β2-tubulin gene has been strongly correlated with high levels of resistance to carbendazim. Removal of the fourth intron in β2tub increases sensitivity to carbendazim in F. graminearum, whereas deletion of the first and second introns enhances β2-tubulin protein expression and consequently reduces sensitivity. This review therefore examines the molecular basis and diversity of resistance mechanisms to benzimidazoles among economically important plant pathogenic fungi.